Earnings management, corporate governance and government equity ownership: empirical evidence from Iraq - Hussein, Noor Abbas (2018)
This study investigates the influence of corporate governance and government equity ownership on earnings management among listed companies in Iraqi Stock Exchange. Specifically, the study examines the audit committee independence, board independence and the existences of government equity participation on earnings management. The study employed data extracted from the annual report of 69 films having the required data for the period of 2012-2015. The study used Panel Corrected Standard Error regression model to the test the association between the variables. The results obtained from the analysis revealed a significant and negative association between government equity ownership, audit committee independence and earnings management. In addition, the results revealed a significant and positive association between board independence and earnings management. To best of the researcher's knowledge, there is little or non-existing literature that examine government equity participation in the Iraqi context. Regulatory authority in Iraq can use the findings of this study to make relevant regulatory pronouncement.